Halal Certification Products and Supporting Tourism Development in Bandung Regency: Issues and Strategies - Evi Sopiah, Evi Sopiah; Nabiela Rizki Alifa; Ismail, Shafinar (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2024)
This research is motivated by the low awareness and compliance of micro and small business actors with halal certification obligations. The research aims to identify the causes or problems of low awareness and compliance with halal certification obligations; and find strategies to increase awareness and compliance with halal certification obligations. This research uses a Community Based Research (CBR) approach, where this approach places MSE actors with researchers and stakeholders in an equal and balanced position. The results of the study found that: first, the factors that influence the low awareness and compliance of Pulosari Village MSE actors with halal certification obligations are low knowledge of halal literacy and low understanding of the requirements and processes of halal certification; and 2) legal counseling strategies and direct assistance to Pulosari Village MSE actors have an effect on increasing awareness and compliance with halal certification obligations. Thus, halal product guarantee law and halal tourism regulations have begun to occupy their role as law in the midst of halal tourism development efforts in Bandung Regency.